2012
DOI: 10.1890/11-1904.1
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the edge effects budget: bay scallop settlement and loss along a seagrass edge

Abstract: Edge effects are a dominant subject in landscape ecology literature, yet they are highly variable and poorly understood. Often, the literature suggests simple models for edge effects-positive (enhancement at the edge), negative (enhancement at the interior), or no effect (neutral)--on a variety of metrics, including abundance, diversity, and mortality. In the marine realm, much of this work has focused on fragmented seagrass habitats due to their importance for a variety of commercially important species. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 48 publications
1
28
2
Order By: Relevance
“…At the microhabitat scale, the positive effect of H. wrightii biomass on species with planktonic dispersal could also be driven by decreased water velocities associated with higher seagrass structural complexity. Some previous studies have found that larval recruitment may be higher within seagrass edge habitats than seagrass interiors (Bologna & Heck, ; Carroll, Furman, Tettelbach, & Peterson, ). While we did not specifically compare edge to interior habitats in this study, we did not find a strong interaction between dispersal mode and seagrass patch size (with smaller patch sizes having higher edge to area ratios).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At the microhabitat scale, the positive effect of H. wrightii biomass on species with planktonic dispersal could also be driven by decreased water velocities associated with higher seagrass structural complexity. Some previous studies have found that larval recruitment may be higher within seagrass edge habitats than seagrass interiors (Bologna & Heck, ; Carroll, Furman, Tettelbach, & Peterson, ). While we did not specifically compare edge to interior habitats in this study, we did not find a strong interaction between dispersal mode and seagrass patch size (with smaller patch sizes having higher edge to area ratios).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in this study we were measuring densities of all benthic life stages and not measuring settlement, per se. Previous studies have found that post‐settlement processes may reverse the relative value of edge and interior habitats as settlement versus juvenile/adult habitat (Carroll et al, ; Hovel & Lipcius, ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from the first experiment suggested that both live oysters and a settlement cue had a negative effect on spat recruitment, and this pattern was confirmed by the second experiment-there was a significant effect of caging. In addition, if survival can be estimated as the ratio between mean values of recruits in open blocks to recruits in caged plots (Carroll et al, 2012;Knights et al, 2012), the results suggest that a settlement cue might increase predatory mortality, particularly in the case of live oysters. Survival was estimated to be 51.9% on live oyster treatments and 70.5% on shells without a chemical cue.…”
Section: Discussionmentioning
confidence: 99%
“…Increased landings in the Napeague area from 2010 to 2013 (3.4 to 6.4% of Peconic estuary totals in 2010, 2011, and 2013, and 35% in 2012, relative ). However, the proportion of 'skunk' scallops, an uncommon color morph that we reared in the hatchery for our OH plantings (Tettelbach et al 2012), was almost twice as high in Napeague Harbor in 2011 compared to baseline proportions in natural populations to the west, despite the fact that the Town of East Hampton did not breed skunks in their hatchery (J. Dunne pers. comm.…”
Section: Temporal and Spatial Differences In Scallop Fishery Landingsmentioning
confidence: 99%
“…For example, at some locations in HB, densities of the mud crab Dyspanopeus sayi averaged 262 ind. m −2 (as quantified using collectors) and very likely exerted intense predation on post-set scallops (Carroll et al 2012). In addition, FB was the only site where the sea star Asterias forbesi was recorded from 2005 to 2012; this species is capable of devastating shellfish beds and restoration efforts (Tettelbach & Wenczel 1993, Hatcher et al 1996.…”
Section: Spatial and Temporal Differences In Scallop Populations Aftementioning
confidence: 99%